Concomitant Versus Individual Administration of Antithrombin and Thrombomodulin for Sepsis-Induced Disseminated Intravascular Coagulation: A Nationwide Japanese Registry Study. (July 2018) - Umemura, Yutaka; Yamakawa, Kazuma; Hayakawa, Mineji; Kudo, Daisuke; Fujimi, Satoshi
Background: Antithrombin and recombinant human thrombomodulin (rhTM) are individually reported to improve survival in sepsis-induced disseminated intravascular coagulation (DIC). However, continuing controversy exists as to which agent is superior and whether concomitant therapy is superior to individual administration. Methods: This post hoc analysis included adult patients with sepsis-induced DIC from a nationwide multicenter registry database in Japan. We categorized patients into 4 groups: patients who received (1) individual administration of antithrombin, (2) individual administration of rhTM, (3) both, and (4) neither. In-hospital mortality was compared between every 2 groups among the 4 groups by Cox proportional hazards model adjusted with propensity scores. Results: In total, 1432 patients with sepsis-induced DIC were included. Although both antithrombin and rhTM were associated better outcome compared with no anticoagulants, mortality benefits were similar between each individual anticoagulant. Similarly, no significant difference in mortality was detected between individual administrations and concomitant therapy. Conclusion: Antithrombin and rhTM might have comparable efficacy in reducing mortality in patients with sepsis; however, concomitant therapy appeared to offer no additional survival benefit.